Multiactivity farm work in the less urbanized contexts of Mexico : 1993 and 2003 - Florez Vaquiro, Nelson; Pacheco Gómez Muñoz, María Edith (CEDUA-COLMEX, 2021)
One of the aspects always mentioned in studies on the economic dynamics of rural contexts in Mexico is the non-exclusivity of a single economic activity. In some studies, this phenomenon is described from the perspective of land use, and in others from the various labor combinations that can be produced in the domestic unit with the idea of explaining forms of social and family reproduction.